2021
DOI: 10.1021/acs.jpclett.1c01884
|View full text |Cite
|
Sign up to set email alerts
|

Guest–Host Interactions in Clathrate Hydrates: Benchmark MP2 and CCSD(T)/CBS Binding Energies of CH4, CO2, and H2S in (H2O)20Cages

Abstract: We present benchmark binding energies of naturally occurring gas molecules CH 4 , CO 2 , and H 2 S in the small cage, namely, the pentagonal dodecahedron (5 12 ) (H 2 O) 20 , which is one of the constituent cages of the 3 major lattices (structures I, II, and H) of clathrate hydrates. These weak interactions require higher levels of electron correlation and converge slowly with an increasing basis set to the complete basis set (CBS) limit, necessitating the use of large basis sets up to the aug-cc-pV5Z and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…We now demonstrate the accuracy and robustness of q-AQUA for standard “stress” tests, namely, the dissociation energies, harmonic frequencies, and diffusion Monte Carlo (DMC) calculations of zero-point energies of isomers of the water hexamer and the dissociation energies of several isomers of the 20-mer, for which benchmark values have recently been reported . We also report molecular dynamics (MD) and path integral molecular dynamics (PIMD) calculations for the radial distribution function (RDF) and MD and semiquantum ring polymer MD (RPMD) calculations of the diffusion constant over a range of temperatures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We now demonstrate the accuracy and robustness of q-AQUA for standard “stress” tests, namely, the dissociation energies, harmonic frequencies, and diffusion Monte Carlo (DMC) calculations of zero-point energies of isomers of the water hexamer and the dissociation energies of several isomers of the 20-mer, for which benchmark values have recently been reported . We also report molecular dynamics (MD) and path integral molecular dynamics (PIMD) calculations for the radial distribution function (RDF) and MD and semiquantum ring polymer MD (RPMD) calculations of the diffusion constant over a range of temperatures.…”
mentioning
confidence: 99%
“…Table shows the binding energies for three isomers of (H 2 O) 20 and compares the benchmark MP2/aV5Z and MP2/CBS calculations with the predictions of q-AQUA and MB-pol. The q-AQUA prediction for the A3 isomer is in good agreement with the MP2/CBS value, whereas the MB-pol value is more than 4 kcal/mol too low.…”
mentioning
confidence: 99%
“…Recently, Heindel et al reported benchmark electronic dissociation energies of several 20mers. 40 This is a stringent test of a FF and this was done for TTM2.1-F and also for the MB-pol FF. For the latter, the energies are roughly 5 kcal/mol lower than the benchmark values.…”
Section: Energies Of Isomers Of the 20-mermentioning
confidence: 99%
“…Finally, the hexagonal sH unit cell is made up of 34 water molecules distributed in three 5 12 , two irregular dodecahedra 4 3 5 6 6 3 (with 20 water molecules) small cages and one large icosahedron 5 12 6 8 (with 36 water molecules) cage. 5,11,12 Less common clathrate hydrates structures, such as the C 0 , C 1 , C 2 , etc. have been also reported.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 These ice-like lattices are naturally occurring in the ocean depths, as well as in permafrost regions of Earth. 4,5 Moreover, they are also likely to exist in other planetary bodies, such as Pluto's ocean, 6 Mars’ ice caps 7 or Titan's surface. 8 The stability of these complexes arises from the hydrogen bonds established between water molecules and the van der Waals (vdW) dispersion forces between host and guest species.…”
Section: Introductionmentioning
confidence: 99%